Resepsi Pembaca terhadap Novel Bercinta dalam Tahajjudku Karya Anshela - Adelina Djauhari; Sayama Malabar; Sitti Rachmi Masie (Ideas Publishing, 2023)
A work can be considered literary if it piques the reader's interest. The study’s objective was to describe the reader's reception of themes, characters, messages, and levels of understanding in the novel BercintaDalamTahajjudkuby Anshela. It applied the qualitative method. Based on findings, the reader’s reception towards the novel’s theme, 66.67% of respondents are interested in the novel, while the reader’s receptions of the character as many as 73.33% stated that its effortless to predict the character of the main character. Further, regarding the readers' perception of the message, as many as 86.67% of respondents claimed that the message could be understood explicitly and implicitly. The reader's level of understanding of the theme, characters, and the message is80%, 67%, and 87%, respectively.